Composite of kaolin/sodium alginate (SA) beads for methylene blue adsorption - Ge, I.T.K. (Gadjah Mada University, 2019)
Dyeing industry is one of the fast-growing industries but at the same time has also brought us a big issue on environment pollution. Adsorption processes is the most effective method in dye removal compared to other methods of wastewater treatment. In recent years, there is an increasing interest in utilizing clay material such as kaolinite as an adsorbent to remove not only inorganic but also organic molecules. In this study, composite of kaolin-sodium alginate (SA) beads was synthesized by varying the weight of kaolin from 0.5 g to 2 g. XRD, FTIR, and surface area analyses were used to characterize the kaolin; while FTIR was used to characterize the composite where the functional groups of kaolin and SA are existing. The amount of 1 g kaolin in SA could improve the adsorption of methylene blue up to 78 of removal after 8 hours. The adsorption model fits pseudo second order kinetic and Langmuir isotherm. Â© 2019, Gadjah Mada University. All rights reserved.